Barbed Wire Border Fencing: Exclusion and Displacement at the Indo-Bangladesh Borderland. (March 2018) - Datta, Abhimanyu
The Government of India decided to fence the entire India–Bangladesh border to prevent the illegal immigration from Bangladesh and to prevent the cross-border illegal and antisocial activities. Since the year 1986, the Government of India started the initiative to construct the border fencing in phase manner. The single wire border fencing which was created in the first phase has been replaced by the composite type of barbed wire border fencing a few years ago. Now the border fencing along the international border between India and Bangladesh has become a structural barrier for the Indian families living at the Country's territorial edge. The families trapped in the geographical space between actual line of partition and the border fencing are living a restricted and deprived life within the limited land. This study is basically focused on the impact of the border fencing on the citizenship rights of the Indian fenced out families. This article will discuss how the defensive policies of the Government are affecting the citizen's rights at the border regions of the country and subsequently resulting in displacement.